PENGGUNAAN MODEL PEMBELAJARAN TALKING STICK BERBANTUAN MEDIA QUESTION CARD TERHADAP HASIL BELAJAR IPA SISWA KELAS III SDN 105337 PANTAI LABU PEKAN - Rossa Aulia Putri Barus; Ryan Dwi Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The science learning process at SDN 105337 Pantai Labu Pekan is still focused on teachers and minimal student participation, which has an impact on low student learning outcomes. To overcome these problems, a learning model is needed that is able to increase student involvement actively, enjoyably and is able to stimulate a deeper understanding of science concepts. One alternative that can be applied is the talking stick learning model assisted by question card media. The purpose of this study was to determine how the use of the talking stick learning model combined with question card media can improve the science learning outcomes of grade III students of SDN 105337 Pantai Labu Pekan. Because the learning outcomes have met the success indicators, this study was carried out using the Classroom Action Research (CAR) approach which was carried out in one cycle. The learning process includes planning, implementing activities, observation and reflection. To assess students' understanding of the material, the assessment instrument used was LKPD. Based on the results of the study, 80.95% of students have met the Minimum Completion Criteria (KKM) with the predetermined values ​​and actively participated in the learning process. Thus, the use of the talking stick model supported by question cards has proven effective in increasing student engagement and science learning outcomes in elementary schools.